Determinants of delayed speech development in African immigrant children in Germany: A scoping review - Jude Tsafack Zefack; Favour Alo Adoche; Fuanyi Awatboh; Brenda Mbouamba Yankam; Cynthia-Edith Ara-Nabangi Ndive; Esua Alphonsius Fotindong (BioSocial Health Journal)
Introduction: Delayed speech development is a prevalent global issue impacting children’s cognitive, social, and academic growth. However, limited research examines speech delays in African immigrant children, particularly in Germany. Cultural, linguistic, and socioeconomic factors play crucial roles in language development within immigrant families. This review explores social determinants contributing to speech delays among African children in Germany and identifies research gaps for future interventions. Methods: A literature search was conducted using PubMed and Google Scholar, focusing on peer-reviewed studies from 2000-2024. Search terms included "Delayed speech," "Speech Development," "African immigrant children," "Socioeconomic factors," and "Germany." The review considered studies involving African children (aged 0–18) in Germany and the social determinants influencing speech delays. Results: African immigrant children in Germany face unique speech development challenges due to socioeconomic, cultural, and linguistic factors. However, research and culturally adapted interventions are scarce, limiting understanding of the prevalence and impact. This review highlights a critical gap, with no targeted studies addressing speech delays in this population, underscoring the need for focused research. Conclusion: Socioeconomic, cultural, and linguistic factors significantly impact speech development in African immigrant children in Germany. Early diagnosis and culturally sensitive interventions are crucial for better outcomes. This review identifies an ‘empty review,’ underscoring the urgent need for longitudinal studies, culturally adapted assessments, and policies to address social determinants and support targeted interventions for improved language development and integration.